Translation - Castor, Laura (Nordlit, 2005)
"Translation" is a life narrative about the ways in which cultural histories shape personal stories, and the capacity of the imagination to develop alternative narratives about oneself and the world. It can also be read a way of addressing the effects of what Ato Quayson calls the global process of postcolonializing. Quaysons critical perspective might be used as an interpretive lens for seeing some of the ways in which this autobiographical narrative complicates the jargon of race, class, gender," terminology which risks reducing the lived experiences of individuals to slogans and ideologies. The narrative considers, imaginatively, the difficulties of cultural translation, and especially some of the inadequacies of thinking in terms of narrow ideologies and national identities at the turn of the 21st century.